(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Background: Ignorance of fasting after acute injury, prior to emergency surgery may cause significant delay in treatment. The aim of this study was to find out the awareness and understanding of “fasting” for anaesthesia after injury. Method: One hundred consecutive patients were evaluated at the time of admission. The following factors were evaluated, cause of intake, patient awareness regarding fasting before anaesthesia and previous history of anaesthesia. Results: Fifty eight males and 42 females with an average age of 41 yrs (range 6-86 years) were included in this study. At time of admission 56 (56%) was fasting and 44 (44%) were not fasting since the injury. Out of 44 who were not fasting 29 (65.9%) ate or drank immediately at the scene of accident, 8 (18%) in Casualty Department, 4 (9%) at home and 3 (6.8%) during transport. Those who took, 32 (73%) patient drank liquids and 12 (27%) patient had both solids and liquids. Those who knew of fasting, 67 had awareness about reason for fasting and 33 did not know what was meant by fasting. 52 patients have previous history of anaesthesia and 48 have no history of previous anaesthesia. Out of 52 patients who previously had anaesthesia for the other surgery, only 28 (54%) were fasting after the injury and rest of them were not fasting. Among 48 patients who had no history of previous anaesthesia only 25 (52%) patient understood the meaning of fasting for anaesthesia. Conclusion: The tradition of giving oral fluids immediately at the scene of accident is still prevalent. This practice can delay the management of acute surgical trauma, affecting the outcome and longer duration hospital stay.